DESIGN EDUCATION FACING THE NEW WORLD - Pamudji Suptandar (Universitas Trisakti, 2005)
AbstractAt least untul the eighteen century it was impossible to separate the artistic content of work of art from its technological structure, for they formed a harmonious and integrated whole. since the industrial revolution however much of art has become somewhat removed from every day culture and form the technological base of contemporary society. Ironically , it is one of the most amazing pieces of technology ever invented that provides the most hopeful prospect of rebuilding the bridge between art and science and the future. Design education is the answer AbstrakSetidaknya hingga abad ke 18, memisahkan muatan listrik dalam suatu karya seni dari sturktur teknologinya adalah mustahil karena keduanya membentuk suatu keharmonisan dan terintegrasi secara menyeluruh. Namun demikina sejak Revolusi Industri banyak karya seni seperti telah terpisah dari budaya keseharian dan dasr-dasar teknologi masyarakat di jamannya. Ironisnya ada satu dari sekian banyak hasil teknologi yang paling mengagumkan pernah ditemukan dan yang memberikan prospek paling menjanjikan dalam membangun kembali jembatan antara seni, ilmu pengetahuan dan masa depan. Pendidikan desain adalah jawabannya